2022
DOI: 10.1002/ppul.26191
|View full text |Cite
|
Sign up to set email alerts
|

Parent's report on oral health‐related quality of life of children with cystic fibrosis

Abstract: Background: Health-related quality of life (HRQoL) scales are now widely used in children with cystic fibrosis (cwCF) which reflects the course of the disease. In this cross-sectional study, our primary aim was to compare the Pediatric Oral Health-Related Quality of Life (POQL) and Oral Health Score (OHS) between cwCF and healthy group. Our secondary aim was to evaluate the association between Pseudomonas aeruginosa (PA) colonization, pulmonary function test, OHS and POQL in cwCF. Methods:The study population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In this context, knowledge of changes in oral health and the dental treatment given to patients have played an important role as they increase understanding about the disease and integrate adequate treatment, which significantly improves quality of life [9] . In addition, studies have shown contradictory results regarding the impairment of oral health in CF patients, such as caries, periodontal disease and changes in both salivary and dental enamel formation [10] .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, knowledge of changes in oral health and the dental treatment given to patients have played an important role as they increase understanding about the disease and integrate adequate treatment, which significantly improves quality of life [9] . In addition, studies have shown contradictory results regarding the impairment of oral health in CF patients, such as caries, periodontal disease and changes in both salivary and dental enamel formation [10] .…”
Section: Introductionmentioning
confidence: 99%